IO2TX / Sharifah Shafinaz Sh Abdullah ... [et al.] - Sh Abdullah, Dr Sharifah Shafinaz; Roslan, Nur Afini Azwa; Ashariman, Nur Alya Nabila; Mohamad Zuki, Nur Mazmira; Omar, Nur Nabila (2021)
Hospital condition is synonymous with a busy environment where there are many patients that nurses should give the services to. The busy schedule makes the nurses not aware to refill the items in the treatment cupboard. Besides, the items in the treatment room are always out of stock when nurses need to use it and have to find the item first. This situation will delay the treatment time and patients should wait for a long time for nurses to prepare for the equipment that they need for a certain procedure. Items out of stock in the treatment room will take a long time to be refilled. Our project, named IO2TX, has been invented to solve this problem. IO2TX is using sensors to detect the quantity of the items such as syringes, needles, alcohol swabs and other items in the treatment cupboard. IO2TX acts as a reminder for nurses when the items in the treatment cupboard went out of stock by action of light-emitting diode (LED) light will blink and display items that are out of stock in the liquid crystal display (LCD) at the cupboard door. Without a device to remind the nurses when the item in the treatment room is near to out of stock, this can lead to hectic conditions when nurses just realize it when they want to provide treatment for the patient. Therefore, the innovation that we created can help nurses be more aware before the items in the treatment room are out of stock. In addition, this will facilitate the work of nurses while having a systematic and manageable system in the hospital. The cost for development of the product is RM100.